2020
DOI: 10.1038/s41467-020-19971-8
|View full text |Cite
|
Sign up to set email alerts
|

Common germline-somatic variant interactions in advanced urothelial cancer

Abstract: The prevalence and biological consequences of deleterious germline variants in urothelial cancer (UC) are not fully characterized. We performed whole-exome sequencing (WES) of germline DNA and 157 primary and metastatic tumors from 80 UC patients. We developed a computational framework for identifying putative deleterious germline variants (pDGVs) from WES data. Here, we show that UC patients harbor a high prevalence of pDGVs that truncate tumor suppressor proteins. Deepening somatic loss of heterozygosity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 77 publications
(140 reference statements)
0
16
0
1
Order By: Relevance
“…However, LOH at a few specific loci is different from generalized LOH produced by mitotic recombination, which entails a loss of complementation for thousands of genes distal to the site of crossing over, including numerous non-driver genes that are essential for the cell [ 62 , 63 , 64 ], and is more likely to be overall deleterious for cells. In tumors, gene expression is higher for genes conserved with unicellular organisms, which have generally systemic effects (such as housekeeping genes) than for genes of metazoan origin [ 65 , 66 ], especially in polyploid cancer cells [ 67 ]; therefore, the coordinated expression of interacting multicellularity and unicellularity processes is lost in cancer progression, and LOH may enhance this mismatch.…”
Section: Discussionmentioning
confidence: 99%
“…However, LOH at a few specific loci is different from generalized LOH produced by mitotic recombination, which entails a loss of complementation for thousands of genes distal to the site of crossing over, including numerous non-driver genes that are essential for the cell [ 62 , 63 , 64 ], and is more likely to be overall deleterious for cells. In tumors, gene expression is higher for genes conserved with unicellular organisms, which have generally systemic effects (such as housekeeping genes) than for genes of metazoan origin [ 65 , 66 ], especially in polyploid cancer cells [ 67 ]; therefore, the coordinated expression of interacting multicellularity and unicellularity processes is lost in cancer progression, and LOH may enhance this mismatch.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the 1000 Genomes Project, the ratio of variants by race was determined [ 55 ]. Associations between somatic and germline variants in several carcinomas have been confirmed using TCGA information [ 56 , 57 , 58 ]. This indicated the interaction of germline-somatic variants in tumorigenesis and assisted in understanding the mechanisms of cancer risk variants.…”
Section: Deposition Application and Indexing Of Genomic Variation Inf...mentioning
confidence: 99%
“…Beyond the direct consequences of LOH on bona fide cancer genes, particularly tumor suppressor genes, numerous non-driver genes located nearby or distally on the same chromosome arm may also undergo LOH. The establishment of LOH maps by cytogenetics [24] or, more recently, by genome-wide copy number analyses and genome sequencing, have enabled identification of chromosomal regions lost in different tumor types [25][26][27][28]. A study of~10 5 LOH events in 363 glioblastoma and 513 ovarian cancer samples revealed that LOH selectively occurs in early replicating regions, especially near RNA pol II-bound transcription start sites [29].…”
Section: Loh Leads To Loss Of Non-driver Genes and Endows Cancer Cells With Unique Vulnerabilitiesmentioning
confidence: 99%